Eksplorasi Etnomatematika: Perbandingan Antara Berat, Volume, Luas Alas, Dan Panjang Bilah Dengan Frekuensi Nada Yang Dihasilkan Pada Saron Nada Slendro - Sari, Putu Purnama; Evangelina, Yohanna Stella Evangelina; Putri, Nadita Dasa Fatmalia (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2022)
“Ethnomathemathics” consists of 3 basic words, namely “ethno”, ”mathema”, and “tics”. Ethnomathematics can be interpreted as mathematics practiced in the culture of society. Saron is one of the gamelan instruments played by being hit, the sound produced comes from the vibration of a metal blade called wilahan. The search method used in this study is a qualitative descriptive method. Ethnomathematics in slendro-tone saron instruments is found in geometric shapes and the relationship between the length, volume, and weight of the blades with their frequency height. The volumenof the blades is calculated with the help of millimeter, while the weight of the blades is calculated with the help of weight scales.